2018
DOI: 10.1186/s40659-018-0194-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of circRNAs involved in the regulation of low nitrogen-promoted root growth in hexaploid wheat

Abstract: BackgroundCircRNAs are widespread in plants and play important roles in response to abiotic stresses. Low nitrogen (LN) promotes the growth of plant root system, allowing it to explore more nitrogen. However, whether circRNAs involved in the response to LN stress and the regulation of LN-promoted root growth in wheat remains unclear.MethodsTwo wheat varieties (LH9 and XN979) with contrasting root phenotypes to LN stress were used as materials to identify circRNAs under control and LN conditions by using high-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…To reveal whether DEcircRNAs can target miRNAs and participate in the transcriptional regulation of genes, we identified 385 DEcircRNAs predicted to contain miRNA decoy sites. As expected, 36 of the 385 DEcircRNAs were predicted to have one to nine miRNA decoy sites, which is consistent with other studies in plants [26,27,57]. For instance, circRNA Chr4:12480688|12481259 has nine miRNA decoy sites, indicating that it might regulate various processes through different miRNAs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To reveal whether DEcircRNAs can target miRNAs and participate in the transcriptional regulation of genes, we identified 385 DEcircRNAs predicted to contain miRNA decoy sites. As expected, 36 of the 385 DEcircRNAs were predicted to have one to nine miRNA decoy sites, which is consistent with other studies in plants [26,27,57]. For instance, circRNA Chr4:12480688|12481259 has nine miRNA decoy sites, indicating that it might regulate various processes through different miRNAs.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, with the development of high-throughput sequencing technology, increasing numbers of circRNAs have been detected in plants and animals. In plants, circRNAs are closely related to plant development and stress responses, including biotic and abiotic stresses [20,[22][23][24][25][26][27][28]30,53]. However, whether circRNAs participate in the pathways of plant responses to hormones is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, circRNAs can function as transcriptional and posttranscriptional regulators, miRNA sponges, small nucleolar RNAs (snoRNAs), RNA processing intermediates, and transcriptional cis-regulators [19][20][21]. Moreover, increasing amounts of evidence have indicated that circRNAs play a key role in plant responses to abiotic stress [20,[22][23][24][25][26]. For example, cir-cRNAs are involved in plant dehydration and immune responses [26], chilling stress [27], heat stress [20], dehydration [28], infection by pathogenic bacteria [19,21], and LP stress [29].…”
mentioning
confidence: 99%
“…Meanwhile, some TaSPL genes were targeted by other miRNAs, such as TaSPL16 and TaSPL13 targeted by miR9780, TaSPL2-B and TaSPL14-D by miR9677b and TaSPL3 by miR319. As reported, miR9780 may be involved in low-nitrogen-promoted root growth [71], miR9677b in pollen development [72] and miR319 in the development of embryo patterning and leaf morphogenesis [73]. These results revealed that complex regulatory network between TaSPL genes and miRNAs affected the potential function of TaSPL genes, which should be con rmed by genetic modi cation in the expression levels of speci c miRNAs or target TaSPL genes of wheat in future.…”
Section: Taspl Genes May Be Targets By Mir156mentioning
confidence: 51%